(untitled) (Homoeopathy for All, 2026)
Oral Submucous Fibrosis (OSMF) is a chronic, progressive, potentially malignant disorder affecting the oral mucosa and is strongly associated with long-term tobacco consumption, spicy food habits, and chronic mucosal irritation. Patients commonly present with recurrent oral ulcers, burning sensation, fibrosis of oral mucosa, halitosis, salivation, and difficulty in mastication. The disease significantly affects quality of life and requires long-term monitoring because of its malignant potential.